DEVELOPING AN ONLINE PRACTICUM EVALUATION MANAGEMENT SYSTEM (Journal of Digital System Development, 2023)
Technology and online systems were enhancing the way people work. An online system for evaluating practicum students is vital as the number of students participating in practicum sessions each semester continues to grow. The traditional method of manual evaluation can be time-consuming and tedious for supervisors, and maintaining and organising student evaluation data can also be a challenge for the university. To overcome these issues, this study aims to create an online evaluation system named "Online Practicum Evaluation Management System". This system will enable supervisors to evaluate students quickly and easily based on the specific rubric without needing to be paper-based. Additionally, the system will provide a secure and organised platform for storing and accessing student evaluation data. This solution aims to enhance the overall efficiency and effectiveness of the practicum program. Rapid Application Developments (RAD) has been used in developing this system. There are four steps in the RAD methodology: requirements gathering, user design, construction, and cutover. Interviews and content analysis were first used to gather the functional requirements. The collected requirements were then used to create a prototype and put through a recorded usability study. The evaluation indicated that OPEMS is practical and straightforward to operate. A majority of respondents are pleased with the system's features. Researchers and developers in this field can use the study as a blueprint for creating similar designs or improving the performance of existing ones. Therefore, the proposed Online Practicum Evaluation Management System will be a more practical, well-organized, faster, reliable, and accurate means of processing the current conventional method of evaluating practicum students.